In a vigilant state of chronic disruption: how parents with a young child with type 1 diabetes negotiate events and moments of uncertainty. Issue 6 (17th June 2020) - Kingod, Natasja; Grabowski, Dan
Abstract: Living as a parent and self‐care surrogate of a young child with type 1 diabetes (T1D) is demanding and a disruption to 'normal' routinised daily living. Research has mainly focused on the time of diagnosis as a one‐time biographical disruption. In this article, we will show how, in the case of families with young children with T1D, the biographical disruption can be viewed as a continuous state of vigilance that affects family functioning and 'normal' living. We will show this by focusing on the temporal events and moments that keep the families in a state of what we will term 'chronic disruption'. The events are the transitions from hospitalisation to home, home to nursery, nursery to daycare, and daycare to school and preparations for social activities concerning the child. The moments are more fluid, ranging from daily interruptions when daycare workers and teachers call parents with doubts about self‐care to negotiations with institutions and municipalities and a constant state of worry.